2014
DOI: 10.4236/ajps.2014.524379
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of UV Light and CO<sub>2</sub> in the Production of Polyunsaturated Aldehydes in <i>Skeletonema costatum</i> (Bacillariophycea)

Abstract: Skeletonema costatum was submitted to two experiments using UV lights and CO2with the purpose of observing changes in the lipids profile and the synthesis of polyunsaturated aldehydes (PUA) after cell disruption. When cells receive CO2 supply, it was noticed that the production of PUA was significantly lower. The same was observed when the culture was treated with a dose of 45.9 kJ•m −2 of ultraviolet A/B ray. The premise to all experiments was the production of 2,4-heptadienal compared to the supply of EPA as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Diatoms are important primary producers in marine settings that produce allelopathic oxylipins when physiologically stressed or wounded by grazing [4][5][6][7][8]45]. Here, we present the first evidence that diatoms also produce these compounds in response to viral infection and the suite of compounds produced likely influence trophic transfer within the microbial loop.…”
Section: Oxylipin Production Was Stimulated By Viral Infection and Di...mentioning
confidence: 80%
See 1 more Smart Citation
“…Diatoms are important primary producers in marine settings that produce allelopathic oxylipins when physiologically stressed or wounded by grazing [4][5][6][7][8]45]. Here, we present the first evidence that diatoms also produce these compounds in response to viral infection and the suite of compounds produced likely influence trophic transfer within the microbial loop.…”
Section: Oxylipin Production Was Stimulated By Viral Infection and Di...mentioning
confidence: 80%
“…The compounds are used as chemical signals across the tree of life, serving as lipid mediators in the human immune system [2] and natural grazing deterrents for land plants [3]. Oxylipin production by diatoms has been specifically tied to copepod [4] and microzooplankton grazing [5], temperature stress [6], UV stress [7], and nutrient stress [8]. Field studies in the Mediterranean Sea have observed increased oxylipin concentrations in association with cell concentration [9], diatom cell lysis measured by staining for membrane integrity [10], and bloom decline [11].…”
Section: Introductionmentioning
confidence: 99%
“…LOX enzymes varied seasonally, potentially explaining variations in PUA production amongst identical strains of diatoms. Additionally, UV stress and growth phase have been observed to impact potential PUA concentrations with more production upon UV irradiation and in stationary phase (Pacheco et al, 2014;. However, the controls on NVO production have not been explored and the controls on PUA production observed in culture and mesocosms have they been thoroughly investigated in situ where 21 feedback loops may exist between the biogeochemical controls on oxylipins and the ecological implications of the bioactive molecules produced.…”
Section: Furthermore Previous Studies That Aimed To Analyze Puas Andmentioning
confidence: 99%
“…The four transects measuring PUAs from large phytoplankton across the North Atlantic showed a good correlation between N:P ratios and potential PUA concentrations . Indeed culture studies have shown that nutrient stress, seasonal variability, and UV irradiation are all associated with altered PUA production upon simulated wounding (Pacheco et al, 2014;). …”
mentioning
confidence: 99%